Effect of adherent Lactobacillus spp. on in vitro adherence of salmonellae to the intestinal epithelial cells of chicken - Jin, Li Zhi; Ho, Yin Wan; Ali, M. A.; Abdullah, Norhani; Syed Salim, Syed Jalaludin (The Society for Applied Microbiology, 1996)
Single strains of Lactobacillus acidophilus and Lact. fermentum, isolated from chicken intestine, were used to study in vitro interactions with Salmonella enteritidis, Salm. pullorum or Salm. typhimurium in an ileal epithelial cell (IEC) radioactive assay. Exclusion, competition and displacement phenomena were investigated by respectively incubating (a) lactobacilli and IEC together, prior to addition of salmonellae, (b) lactobacilli, IEC and salmonellae together, and (c) salmonellae and IEC, followed by the lactobacilli. Lactobacilli were selected for study because of their strong ability to adhere to IEC and poor aggregation with salmonellae. The results demonstrated that Lact. acidophilus significantly reduced (P < 0.05) the attachment of Salm. pullorum to IEC in the tests for exclusion and competition, but not in the displacement tests. Lactobacillus fermentum was found to have some ability to reduce the attachment of Salm. typhimurium to IEC under the conditions of exclusion (P < 0.08), competition (P < 0.09), but not displacement. However, both Lact. acidophilus and Lact. fermentum were unable to reduce the adherence of Salm. enteritidis to IEC under any of the conditions.